Kinome analyses of inflammatory responses to swine barn dust extract in human bronchial epithelial and monocyte cell lines. Issue 6 (August 2018) - Nath Neerukonda, Sabari; Mahadev-Bhat, Sanjana; Aylward, Bridget; Johnson, Casey; Charavaryamath, Chandrashekhar; Arsenault, Ryan J
Exacerbated inflammation upon persistent barn organic dust exposure is a key contributor to the pathogenesis of lung inflammation and lung function decline. Barn dust constituents and the mechanisms contributing to the exacerbated inflammation are not clearly known. We set out to understand the inflammatory effects of Swine Barn Dust Extracts (SBDE) on human lung epithelial (BEAS2B) and macrophage (THP-1 monocyte derived) cell lines on a kinome array to determine phosphorylation events in the inflammatory signaling pathways. Upon identifying events unique to SBDE or those induced by innate immune ligands in each cell line, we validated the signaling pathway activation by transcriptional analyses of downstream inflammatory cytokines. Our findings indicate that SBDE-mediated pro-inflammatory effects are predominantly due to the induction of neutrophilic chemokine IL-8. Differentially phosphorylated peptides implicated in IL-8 induction in BEAS2B cell line include, TLR2, 4, 5, 7, 8, 9, PKC, MAP kinases (p38, JNK), inflammasomes (NLRP1, NLRP3), NF-κB and AP-1. In the THP-1 cell line, in addition to the aforementioned peptides, peptides corresponding to RIG-I-like receptors (RIG-I, MDA5) were found. This is the first report to demonstrate the application of a kinome array to delineate key inflammatory signaling pathways activated upon SBDE exposure in vitro .